A training module to empower marginalised Northern Borneo islanders for tuberculosis control - Mohammad Saffree Jeffree; Fatimah Ahmedy; Mohd Yusof Ibrahim; Khamisah Awang Lukman; Kamruddin Ahmed; Nelbon Giloi; Daw Khin Saw Naing; Aza Sherin Yusuff (pagepress, 2020)
Empowering marginalised urban islanders with limited heatlh accessibility for controlling pulmonary tuberculosis (PTB) requires a specific training module. Developing a training module for knowledge transfer to empower these marginalised islanders in high PTB occurrence region can be adapted based on IMCI framework. Structuring knowledge and skills for PTB control is based on the National Strategic Plan for Tuberculosis Control 2016-2020 and the Integrated Management of Childhood Illness (IMCI) framework is adapted for developing the training module. A total of five knowledge and skills were structured: 1) PTB disease and diagnosis, 2) PTB treatment, 3) preventive PTB measures, 4) prevention of malnutrion, and 5) psychosocial discrimination. The IMCI framework was adapted in 3 ways: 1) identifying signs and symptoms of PTB, 2) emphasising 5 steps: assess, diagnose, treat, counsel and detect, as the integrated management, and 3) counseling on BCG immunisation, malnutrition, environmental modifications and stigma on PTB.